Self-regulation of learning and its relationship to implicit intelligence among female kindergarten students - ReyamSaadDaoudProf. Bushra Hussein (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Students at all levels of study suffer from general weakness in academic achievement, despite the fact that a large number of these students possess mental abilities that enable them to achieve educational goals and achieve reasonable and acceptable grades. The reason behind students’ weakness and failure to achieve outstanding academic achievement may be due to the failure of the organization process. They have self (Kassab, 2015:1(